Dekonstruksi pada Peran Tokoh Utama dalam Novel Rabet: Runtuhnya Jerman Timur Karya Martin Jankowski - Yustinus Budi Setyanta (DIALEKTIKA: Jurnal Ilmiah Pendidikan Bahasa, Sastra, dan Matematika, 2015)
Deconstruction is a method of reading the text very carefully to find inconsistencies and paradoxes in the concepts of the text as a whole by turning the existing oppositions. The elements are deconstructed is the element that determines the text. Deconstruction on the main prominent role in novel Rabet: Runtuhnya Jerman Timur by Martin Jankowski generate some binary opposition, i.e., capitalist-socialist, West German-East German, rich-poor, rebel-fighters, and cage-palace. Results deconstruction of the Socialist paradox shows that the main character misinterprets binary opposition between the capitalist and socialist because actually, socialists higher rank than capitalist. Results deconstruction of the paradox of East Germany, the main character misinterprets binary opposition between East Germany and West Germany because of East Germany get a higher place than West Germany. Results deconstruction of the paradox of poor, indicating that the main character misinterprets binary opposition between rich and poor because in fact, the people of East Germany was not poor. Results deconstruction of the paradox fighters showed that the main character as a representation of a warrior, it turns out, when viewed from the side of the East German government, as rebels because the East German government actually was a good purpose for its citizens, which is making its citizens prosper. Results deconstruction of the paradox enclosure indicates that the main character is not actually born in a stable because of the fact that the East German government to the welfare or well-being to its citizens.